Oil palm fiber vinylester composite; Effect of bleaching treatment - Nabinejad, O.; Debnath, Sujan; Mohsen Taheri, M. (2017)
The aim of this paper is to investigate the effect of chemical treatment on the flexural properties of the composite. Oil Palm Empty Fruit Bunch Fibers (OPEFB) reinforced Vinylester composite were prepared in this study. Soxhlet extraction together with sodium hypochlorite bleaching methods was used for chemical treatment. The diameter of fibers was reduced from a range of 250-350 µm to 10-15 µm by treatment. Shape and texture of the fibers transformed from solid brown colored strings into a white gel. Thermogravimetric Analysis (TGA) test was carried to investigate the effect of treatment on the thermal properties of natural fibers. Vinylester composites were fabricated using untreated and bleached OPEFB fibers. The bending test results showed the bleached fibers displayed greater flexural properties compared to untreated fibers, where the time of bleaching was an important factor in the treatment process.